The Effect of Work-Life Balance on Workers in Nagan Raya District - Meriyana Meriyana; Hamdi Hermen; Muhammad Rahmat Hidayat; Ivon Jalil; Rusdi Rusdi (PT. Intelek Cendikiawan Nusantara, 2026)
This study aims to analyze the effect of Time Balance (X1), Involvement Balance (X2), and Satisfaction Balance (X3) on Work Life Balance (Y) among employees in Nagan Raya Regency. The research employs a quantitative correlational approach to examine the relationships between variables. The study sample consisted of 384 respondents, determined using Cochran’s formula and selected through a stratified random sampling technique. Data were collected through questionnaires, and data analysis was conducted using multiple linear regression with the assistance of SPSS software. The results indicate that, partially, Time Balance (X1), Involvement Balance (X2), and Satisfaction Balance (X3) have a positive and significant effect on Work Life Balance (Y), with significance values of 0.000 < 0.05. Simultaneously, the three independent variables significantly contribute to Work Life Balance, with a coefficient of determination (R²) of 0.808, meaning that 80.8% of the variation in Work Life Balance can be explained by these three variables, while the remaining 19.2% is influenced by other factors outside the research model, such as organizational support, company policies, individual characteristics, and employees’ psychological and social factors. The findings emphasize the importance of effective time management, involvement in social roles, and satisfaction with the balance between work and personal life in enhancing employees’ Work Life Balance.